NO DISRUPTION – ONLY EXPOSURE! A CRITICAL ANALYSIS OF CROSS-MEDIA DYNAMICS IN DUTCH MEDIATIONS OF SEXUAL MISCONDUCT - Burkhardt, Sarah (AoIR Selected Papers of Internet Research, 2026)
Social media have become a popular object of public debate in which they are often blamed for substantially causing socio-political rupture, such as the current “return” of racist and fascist sentiments across Europe. While much attention has been paid to social media, the important role of national legacy media and their potentially nurting role for such “ruptures” is often overlooked and still understudied.Focusing on the mediation of sexual misconduct in the Netherlands, this paper therefore critically examines how social media and national legacy media intersect in collectively maintaing cultural issues that social media exposure turns into perceived “ruptures” across Western countries.For operationalizing the analysis, the paper departs from the Dutch cross-media research infrastructure project Twi-XL which grants access to different archival media collections. Leveraging television transcripts from 1981 until 2023 and Dutch tweets from 2011 until 2023, the paper introduces a methodological framework with topic modeling for systematically tracing how the “overexposure” of certain issues on social media has potentially emerged through their “underexposure” on television over time.The paper finds that Dutch television paid ample attention to the internal, structural and complex dimensions of sexual misconduct. While Dutch television historically framed sexual misconduct within institutional contexts from a progressive and feminism-oriented agenda, it neglected any critical and in-depth engagement alongside the axes of race and gender. Conversely, Dutch Twitter—particularly since the 2015 European “refugee crisis”—externalized the issue, reducing its complexity and often appropriating feminist paradigms and wordings to advance Islamophobic and far-right discourse.